Probation aspects of administrative contentious action and sponsored interest patterns - Méndez Maúrtua, Miguel Ángel (2018)
The objective of this research is to determine, about the class action, the lack of evidence, due to the negligence of the plaintiff, a lot of class action was declared dismissed, which prevent back to sue. The methods used were: inductive and deductive, based on the analysis of case law and interviews with judges of the, North Lima Court and North Lima District Attorney from the analysis of judgments of class action’s cases; also method used was qualitative to analyze the different approaches taken by the jurisprudence and law doctrine. In addition, it will also seek to establish the active procedural legitimacy of public institutions that are in a position to defend diffuse and collective interests within our procedural system. It has been found that a lot of judicial procedures, that were analyzed above, were dismissed, because the lack of evidence to support the claim suitable, causing harm to the society. Besides, a lot of Constitutional Court’s precedents are not duty to obey them for the judicial branch, and also we have the fact about of the lack of regulation in the law, this situation implies a minimum liability of the justice to point out that the court had expired the applicant on a common cause another member of society can sue again, for it must be regulated.